Androcentrism Inequality between Men and Women in the Film 'Moxie' - Fathurokhmah, Fita; Aini, Sari Khurul; Fitriadi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
The Film 'Moxie' raises the issue of gender inequality between men and women. This film depicts teenage girls who dare to rebel against the inequality of androcentrism towards women and fight for gender equality in their school, which is still biased towards male norms. This research question concerns the critical discourse on the inequality of androcentrism between men and women in the Film 'Moxie'. What are the subject and object of the story? Betty Friedan's feminist theory uses the concept of androgyny as a reference because of the similarity in roles between men and women. Sara Mills' critical discourse analysis research method focuses on how women are presented in the text and divided based on the subject-object of the story and the viewer's position related to the issue of androcentrism inequality: critical research paradigm and qualitative descriptive approach. The results of these findings are, first, the inequality of androcentrism between men and women in this film, namely the presence of Misogyny, namely hatred and dislike of women, negative stereotypes, and double standards. Second, in the Film 'Moxie', the subject position of the story is Vivian, and the object position of the story is Vivian's female and male friends at Rockport High School and Principal Shelly. The viewer is positioned as the woman. Androcentrism means male-centered. Androcentrism refers to the pattern that everything related to men is the general guideline, while everything related to women is only an exception. The theoretical implications of this research strengthen the concept of androgyny and criticize the inequality of androcentrism for showing the distribution of equal roles in masculine and feminine characters simultaneously at various levels of life.